Optimalisasi Pemahaman Dasar-dasar Fotografi melalui Model Pembelajaran Berbasis Masalah (PBL) dengan Pendekatan Pembelajaran Berdiferensiasi dan Quizziz di SMKIT Robbani Singosari - Yulfidya, Dwi Erma; Saputra, Bachtiar Adi (Al-DYAS, 2024)
This research investigates the effectiveness of implementing the Differentiated Learning Approach and the Quizziz platform to enhance the understanding of the fundamentals of photography at the Robbani Singosari Integrated Islamic Elementary School (SDIT) level. Challenges in photography learning, such as passive student engagement, an inadequately conducive learning environment, difficulty comprehending the material, monotonous teaching methods, and the incongruity of media with student characteristics, serve as the backdrop for this study. The incorporation of the Differentiated Learning Approach facilitates the adjustment of material to accommodate diverse learning styles, addressing the challenges encountered in the learning process. Additionally, the study centers on the utilization of Quizziz as an evaluative tool, revealing students' positive responses to the engaging and interactive learning experience facilitated by the platform. The research findings underscore the substantial role of the Differentiated Learning Approach in augmenting learning efficacy, particularly in surmounting obstacles to material comprehension and establishing an inclusive learning milieu. The employment of Quizziz as an assessment tool not only validates its effectiveness in gauging student comprehension but also introduces an entertaining and interactive facet that enriches the overall learning experience. This study aligns with prior research affirming the constructive influence of the Differentiated Learning Approach and the amalgamation of online platforms in fostering heightened student interest and engagement. Implications of these findings encompass recommendations for refining learning strategies at the elementary school level, especially within the context of photography education. The integration of the Differentiated Learning Approach and Quizziz is anticipated to make a significant contribution to enhancing student comprehension and cultivating a more gratifying learning experience in the current digital era.